2016
DOI: 10.3390/rs8090740
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm for Automatic Road Asphalt Edge Delineation from Mobile Laser Scanner Data Using the Line Clouds Concept

Abstract: Accurate road asphalt extent delineation is needed for road and street planning, road maintenance, and road safety assessment. In this article, a new approach for automatic roadside delineation is developed based on the line clouds concept. The method relies on line cloud grouping from point cloud laser data. Using geometric criteria, the initial 3D LiDAR point data is structured in lines covering the road surface. These lines are then grouped according to a set of quasi-planar restriction rules. Road asphalt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…The combination of such data with ALS data sets allows automated 3D modeling and keeping maps updated. Algorithms have been developed for extracting road markings [57], curbs [80], road edges [81], and pole-like objects [82] from MLS data. For dense MLS data sets, methods for automatic identification and segmentation of various urban furniture have been developed [83,84].…”
Section: Built and Road Environmentsmentioning
confidence: 99%
“…The combination of such data with ALS data sets allows automated 3D modeling and keeping maps updated. Algorithms have been developed for extracting road markings [57], curbs [80], road edges [81], and pole-like objects [82] from MLS data. For dense MLS data sets, methods for automatic identification and segmentation of various urban furniture have been developed [83,84].…”
Section: Built and Road Environmentsmentioning
confidence: 99%
“…Various studies were carried out in the past years (Zai et al, 2018, Soilán et al, 2017. Nevertheless, the prior knowledge about LiDAR-derived control point selection makes the accurate driving line generation very challenging (Cabo et al, 2016). Therefore, developing an efficient and robust algorithm to generate driving lines while precisely recording their geometry and coordinate information from large-scale and unordered MLS point clouds, has been essentially needed.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a cost-effective traffic sign inventory method was proposed in Ai and Tsai, (2015). In parallel, Cabo et al, (2016) applied an automatic algorithm to detect road asphalt edge limits for road maintenance and safety assessment. An adequate review of the scientific literature can be found in Yang et al, (2013).…”
Section: Introductionmentioning
confidence: 99%